Visual Judaism in late antiquity: historical contexts of Jewish art - Leṿin, Yiśraʾel L. (Yale Univ. Press, 2012)
Introduction. Ancient Jewish art: a century of research -- Early historical contexts. Israelite art -- Art in the Second Temple period and its aftermath -- New expressions of Jewish art in the late Roman era. The emergence of Jewish art in the third century -- Dura Europos in its Eastern religious setting -- Bet Sheʻarim in its patriarchal context -- The Jewish catacombs of Rome and their Roman and Christian parallels -- The third century in retrospect -- Late antiquity in Jewish history: a significantly altered historical perspective. The Byzantine period: old, new, and recent views -- The Byzantine-Christian period and its impact on Jewish culture -- The flourishing of Jewish art in the Byzantine-Christian era. Synagogue art in late antiquity: an overview -- Ḥammat Tiberias and its patriarchal-aristocratic setting -- Sepphoris in its priestly context -- Bet Alpha in its sixth-century Christian milieu -- Sardis: prominence and stability in the Jewish diaspora -- Art-historical issues. The zodiac and other Greco-Roman motifs in Jewish art -- Religious components of Jewish art and synagogue sanctity: diachronic and synchronic factors -- Modern metatheories in the interpretation of Jewish art -- Art and society. The communal dimension of synagogue art and other related contexts -- Art and the rabbis -- Art, the patriarchs, and the urban aristocracy -- Art and Jewish identity in late antiquity